THE EFFECT OF DIGITAL LITERACY SKILLS ON IMPROVING TEACHER CREATIVITY - Zayas, Juan David Martinez; Rofi'ah, Nurhayati (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
The current education requires a new teaching approach based on digital literacy because today’s students experience different needs based on the technological era. To face this reality, teachers must be creative because technology is changing so fast and students’ digital literacy are more advanced than their educators. A good way how to develop teachers’ creativity is by introducing a digital literacy education program for preservice and in-service teachers from different levels. This research paper is conducted by theoretical research method. Data are collected by a theoretical review technique. Also, this research design is based on a descriptive approach. The study is focused on teachers’ creativity development by increasing digital literacy. Papers related to the topic under study were searched on educational journals.  The main goal of this paper is to find out how digital literacy skills influence educators’ creativity development. Findings show that the use of technology develops various skills such as problem-solving, productivity, collaborative imagination, curiosity, and other factors that increase creativity. Current researchers also find that technology enhances teachers’, motivation, cooperation, and creation.  Overall, children of this age are involved with technology every day, and for them is almost natural to deal with this reality, for this reason, this paper suggests that digital literacy skills must be inculcated in teachers from all levels by different methods to face the reality.